Masjid Lama Gang Bengkok: Menyusuri Sejarah dan Keunikan Arsitektur di Kota Medan - Ardiansyah, M. Rasyid; Padang, Perjanggut Emas; Afrian, Riski; Siregar, Yusra Dewi (Medan Resource Center, 2024)
The Old Mosque of Gang Bengkok is one of the historical sites in Medan that reflects the fusion of Malay and Chinese cultures. This mosque not only serves as a place of worship but also stands as a witness to the development of Islam in Medan. This study explores the historical traces of the mosque's establishment, its socio-cultural influences during the colonial period, and the uniqueness of its architecture, which combines traditional Malay elements with distinctive Chinese ornaments. The research employs a qualitative method with a historical and architectural approach to uncover the symbolic meanings of the mosque's architectural features. The findings reveal that the Old Mosque of Gang Bengkok is not just a spiritual site, but also a reflection of intercultural harmony and an important historical legacy for the people of Medan.